Dietary Patterns and Dietary Recommendations Achievement From Latin American College Students During the COVID-19 Pandemic Lockdown - Murillo, Ana Gabriela (2022)
This study aimed to compare the diet quality of different dietary patterns among college students from Latin American countries, including vegetarians, vegans, and omnivores during the COVID-19 pandemic. A cross-sectional, observational, multicenter study was conducted including a non- probabilistic sample of university students from 10 countries. University students were invited to participate in the study through social network platforms. Participants were self-reported to have followed a specific dietary pattern; either the Prudent diet, Western diet, Ovo-dairy-vegetarian diet, Fish-vegetarian diet, Strict vegetarian diet (vegan) or other. The last three patterns (vegetarians and vegans) were grouped as following a plant-based diet. A self-assessment survey was used to evaluate healthy eating habits using a questionnaire with values between 1 (do not consume) and 5 (consume) for a total of 9–45 points (higher values represent better eating habits). Unhealthy habits were assessed with nine questions. A total of 4,809 students filled out the questionnaire, and the majority of them were females (73.7%). A high percentage have been in lockdown for more than 5 months and were in lockdown when the survey was released. 74.3% were self-reported to follow a prudent diet, while 11.4% reported following a western dietary pattern and 8.8% a plant-based diet. When compliance with healthy and unhealthy dietary habits was analyzed, although all groups had low compliance, the plant-based diet group (56.09 ± 6.11) performed better than the Western diet group (48.03 ± 5.99). The total diet quality score was significantly higher for plant-based diet followers, who also tended to better achieve the recommendations than omnivorous students, especially the ones following a western diet. These results present evidence that young adults such as college-aged students have unhealthy dietary habits. However, the ones who follow a plant-based diet such as vegetarians and vegans exhibit better scores and healthier dietary conducts.